Value Added Analysis of Pineapple Leaf-Waste Products and Strategic Development for Miwa Producer Cooperative in Prabumulih - Purbiyanti, Erni; Sari, Yulia; Sulastri, Merna Ayu; Putri, Trisna Wahyu Swasdiningrum; Adzra, Ghaitsa Safira (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
Pineapple leaf waste (PALW) is often perceived as an agricultural by-product with limited utility and lacking economic value. This study pioneers the evaluation of added value from pineapple leaf waste in Prabumulih. It explores innovative strategies for developing the Wiwa Producer Cooperative using the Hayami method and SWOT analysis. The findings reveal that all processed products, such as woven fabric and cloths, derived from pineapple leaf waste generated a high and profitable value-added ratio. A key strength factor is that the Miwa Pineapple Producer Cooperative is a pioneer of pineapple leaf processing in Prabumulih. However, significant weaknesses include limited human resources and capital, while opportunities exist in promotional events, and threats arise from the lengthy production process. The cooperative adopts an aggressive strategy, emphasising market penetration, market development, and product innovation through the Strengths-Opportunities (S-O) approach. The findings underline the economic potential of pineapple leaf waste as a sustainable resource, offering a pathway to rural economic empowerment and environmental conservation. This study provides actionable strategies for policymakers and cooperative leaders to enhance competitiveness, foster innovation, and promote sustainable practices in the agricultural sector. By participating in broader promotional events, maintaining product quality, expanding market reach, and innovating product offerings, the cooperative can ensure sustainable growth and contribute to the circular economy.